POLA PENGASUHAN ORANGTUA DALAM MEMBENTUK ANAK PENGHAFAL AL-QUR’AN DI KECAMATAN CITEUREUP KABUPATEN BOGOR - Samsuddin; Akbar Maulana; Agus Sarifuddin (As-Sulthan Journal of Education, 2025)
This study examines the role of parental upbringing in shaping children as Qur’an memorizers in Citeureup District, Bogor Regency. The research employs a descriptive qualitative approach with a case study method, focusing on parental upbringing patterns in forming Qur’an memorizers in Puspasari village and Puspanegara sub-district, Citeureup District. Data sources were collected through observation, interviews, and documentation techniques. The data were analyzed using data reduction, data presentation, and conclusion drawing methods. The findings reveal that authoritarian and democratic parenting styles are the primary approaches implemented. The authoritarian style emphasizes discipline through strict rules, while the democratic style focuses on balancing freedom and emotional support. Both styles are effective with their respective strengths: the authoritarian style supports the achievement of memorization targets through discipline, whereas the democratic style fosters intrinsic motivation and harmonious relationships between parents and children. The study also found that selecting a parenting style must consider the child’s individual characteristics to achieve optimal results. Furthermore, proportional control and consistency in parenting application are key to successfully nurturing Qur’an memorizers. The implications of this research highlight the importance of collaboration between parents, teachers, and educational institutions in supporting Qur’an education processes. Recommendations are provided for parents to integrate authoritarian and democratic approaches flexibly, for educational institutions to provide Islamic parenting training, and for future researchers to explore the long-term impact of parenting on children’s education.